Allograft Outcomes in Outbred Mice. Issue 3 (11th January 2013) - Reichenbach, D. K.; Li, Q.; Hoffman, R. A.; Williams, A. L.; Shlomchik, W. D.; Rothstein, D. M.; Demetris, A. J.; Lakkis, F. G.
<x xml:space="preserve">Abstract</x> Inbreeding depression and lack of genetic diversity in inbred mice could mask unappreciated causes of graft failure or remove barriers to tolerance induction. To test these possibilities, we performed heart transplantation between outbred or inbred mice. Unlike untreated inbred mice in which all allografts were rejected acutely (6–16 days posttransplantation), untreated outbred mice had heterogeneous outcomes, with grafts failing early (<4 days posttransplantation), acutely (6–24 days) or undergoing chronic rejection (>75 days). Blocking T cell costimulation induced long‐term graft acceptance in both inbred and outbred mice, but did not prevent the early graft failure observed in the latter. Further investigation of this early phenotype established that it is dependent on the donor, and not the recipient, being outbred and that it is characterized by hemorrhagic necrosis and neutrophilic vasculitis in the graft without preformed, high titer antidonor antibodies in the recipient. Complement or neutrophil depletion prevented early failure of outbred grafts, whereas transplanting CD73‐deficient inbred hearts, which are highly susceptible to ischemia‐reperfusion injury, recapitulated the early phenotype. Therefore, outbred mice could provide broader insight into donor and recipient determinants of allograft outcomes but their hybrid vigor and genetic diversity do not constitute a uniform barrier to tolerance induction.